Chinese Migrants' Sense of Belonging in Japan: Between Digital and Physical Spaces - International Organization for Migration (United Nations, 2020)
Authored by Xinyu (Promio) Wang, this Migration Research Series paper explores what belonging means and entails for Chinese migrants in Japan in today’s digitalized societies. Drawing on interviews with 55 Chinese migrants in Japan between 2017 and 2019, the paper highlights the impact of digital technologies on fostering a sense of belonging to a transnational imagined community. It also sheds light on how the interactions of the digital and physical spaces have framed a multidimensional sense of belonging for Chinese migrants in Japan.